Evaluation of Commercial Strains of Torulaspora delbrueckii in Beer Production. (3rd April 2023) - Drosou, Fotini; Anastasakou, Katerina; Tataridis, Panagiotis; Dourtoglou, Vassilis; Oreopoulou, Vassiliki
Abstract: Nowadays, the micro-brewing industry aims at yeast strains beyond Saccharomyces cerevisiae, the so-called non- Saccharomyces, for their flavor contribution to the final product. In the present study, two commercial strains of Torulaspora delbrueckii (Prelude and 291) were evaluated for the production of a pale ale beer, in mono- and co-culture fermentations with S. cerevisiae, at 13 and 20 °C. From the results, it was concluded that both non- Saccharomyces yeasts were able to metabolize wort sugars at both temperatures, albeit at a slower rate at 13 °C. The fermented products were sealed in glass bottles (without filtration) and measurements of the ethanol content, color, bitterness, and volatile compounds were conducted after 30 days of storage. The ethanol content obtained from the non- Saccharomyces monocultures varied between 3.90 and 5.50% alcohol by volume (ABV), while that of the co-cultures was not significantly different from the ethanol content obtained by the conventional yeast (4.80–5.80% ABV). Higher bitterness and color values were detected in the non- Saccharomyces fermentations. The analysis of volatile compounds revealed that the two non-conventional yeasts were capable of producing aromatic components, such as higher alcohols and esters, yielding a fruity and floral aromatic profile, especially in the mixed culture fermentation of T. delbrueckii 291 at 13 °C.